Soft Gelatine Capsules- Critical Quality Attributes of Chosen Excipients and Capsules Parameters Following the Quality by Design Concept - Barbara Owczarek; Edyta Łukowska-Chojnacka (Polskie Towarzystwo Farmaceutyczne, 2023)
Soft gel capsules are a common form of medicine and food supplements. Quality, productivity and manufacturing time is crucial for producers during their development and industrial operations. To ensure the best quality of the product, it is necessary to know all critical process steps and parameters. The use of QbD elements is to ensure the quality of the drug product throughout its "life cycle". Quality by design (QbD) and its elements are described by the International Council of Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) and in their guideline - chapter ICH Q8 (Pharmaceutical Development). One of the first steps in pharmaceutical product development is to prepare Quality Target Product Profile (QTPP) and analyse Critical Material Attributes (CMAs) and Critical Quality Attributes (CQAs) of excipients, active pharmaceutical ingredient (API) and final product. During this research, we investigated the CQAs of the excipients used in vitamin D3 soft gelatin capsules containing high doses of cholecalciferol, from 10 000 to 200 000 IU per capsule. We considered the viscosity of the gelatin mass, the effect of the addition of dye on the viscosity, and the impact of the colour of the gelatin mass on the active substance content in the final capsules. It was also investigated oily carriers (medium chain triglycerides and safflower oil) and antioxidants (alpha-tocopherol acetate vs butylhydroxytoluene), and their effect on API concentration in the capsule.